Implementation of the Full Costing Method in Determining Application-Based Selling Prices to Improve Financial Recording Performance in Dodol Sukahati MSMEs, Cibinong District Bogor Regency - Hamzah, Zeze Zakaria; Anwar, Syaiful; Hamdani, Muchamad; Muhlis, Muhlis; Subagyo, Wawan Hari; Mujito, Mujito (LPPM UIKA Bogor, 2024)
Dodol MSMEs are one of the MSMEs that support the national economy. it is located in Sukahati Village, Cibinong District, in calculating production costs is still traditional, so the selling price is still traditional. In this all-digital era, these MSMEs need to adapt to the times. In facing the development of the times and maximizing finances, it is necessary to carry out community service so that MSMEs, especially Dodol MSMEs, have financial capabilities that can maintain the sustainability of their business. These MSMEs need to be briefed related to simple financial records, production cost calculations, and sales calculations to use applications to find out the profits obtained. The method is used Participatory Action Research (PAR) which focuses on empowering the community and involving them in the process of change. This activity, which runs from June to August 2024, includes ongoing monitoring and evaluation. It is hoped that from this activity, Dodol MSMEs can calculate production costs and use the applications that have been made in this service.